EFEKTIVITAS KONSELING KELOMPOK RATIONAL EMOTIVE BEHAVIOR THERAPY TERHADAP EFIKASI DIRI SISWA MENGHADAPI UJIAN KENAIKAN KELAS - Nurjannah, Aulia; Dina Hajja Ristianti; Aida Rahmi Nasution; Syamsul Rizal (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aimed to examine differences in students' self-efficacy before and after group counseling using Rational-Emotive Behavior Therapy (REBT) with the rational role-reversal technique in facing the class-promotion examination at SMA Negeri 4 Rejang Lebong Regency. A pre-experimental one-group pre-test–post-test design was used. The population consisted of 120 grade X students, from whom 10 students indicated to have low self-efficacy were selected through purposive sampling as the research sample. The intervention consisted of four group counseling sessions, one session per topic, each lasting 1 × 60 minutes, held between February and May 2025. Data were collected using a 31-item self-efficacy questionnaire and analyzed using a paired-sample t-test and N-Gain test. Results showed that the mean N-Gain score before the intervention was 0.01 (low category), while the mean N-Gain score after the intervention increased to 0.62 (moderate category), indicating a moderate effect size according to Hake's (1998) criteria. The paired t-test produced t = 2.491 (df = 9) with a significance value of 0.000 (p < 0.05), exceeding the critical value of t-table = 2.262, indicating a significant difference between students' self-efficacy before and after the REBT group counseling. These findings suggest that REBT group counseling using the rational role-reversal technique is effective in improving students' self-efficacy when facing academic examinations, although the small sample size and absence of a control group limit generalization of the results.